Flotação de minério de ferro dolomítico - Leandro Seixas Bicalho (2019)
Quadrilátero Ferrífero is an important mineral province located in Minas Gerais state, responsible for the greatest part of iron production in Brazil. Among the concentration methods for iron ore practiced by the companies with activities in this region, the most important is the reverse cationic flotation. In conventional processes, quartz is the main gangue mineral and with the use of cationic collector such as alkyletheramines it is easily floated allowing the concentration of the iron-bearing minerals. Dolomite iron formations, with the presence of hematite, quartz and dolomite, are present in several areas of mining and, with the deepening of the iron ore deposits, this type of ore with low iron content and more complex mineralogy is increasingly recurrent. Carbonaceous minerals, mainly dolomite, present a technological challenge for the concentration of iron ore by flotation. In the present study, it was evaluated the concentration of an iron ore with 6% of dolomite content. The bench flotation tests showed that conventional reverse cationic flotation is not selective to float dolomite, thus compromising the iron content in the final concentrate. Different flotation routes were evaluated, and a selective condition was reached to float both quartz and dolomite using the combination of the cationic collector FLOTIGAM 16424 with an anionic collector FLOTINOR 16551. It was demonstrated that the flotation of dolomite is favored with a combination between both collectors in the cleaner stage, and by a previous quartz flotation in the rougher stage. Zeta potential analysis and infrared spectrometry measurements indicated the chemisorption as the adsorption mechanism between FLOTINOR 16551 and dolomite, confirming the high selectivity observed in the bench flotation tests.